Testing the Production Approach to Markup Estimation - Raval, Devesh (Review of Economic Studies, 2023)
Abstract Under the production approach to markup estimation, any flexible input should recover the markup. I test this implication using manufacturing datasets from Chile, Colombia, India, Indonesia, the U.S., and Southern Europe, as well as store-level data from a major U.S. retailer, and overwhelmingly reject that markups estimated using labour and materials have the same distribution. For every dataset, markups estimated using labour are negatively correlated with markups estimated using materials, exhibit greater dispersion, and have opposite time trends. I continue to find stark differences in markups estimated using energy and non-energy raw materials. Non-neutral productivity differences across firms can explain these findings.